Blinatumomab, a bispecific B-cell and T-cell engaging antibody, in the treatment of B-cell malignancies. Issue 3 (4th March 2019) - Burt, Richard; Warcel, Dana; Fielding, Adele K.
ABSTRACT: Blinatumomab (Blincyto, Amgen), a bi-specific antibody, is a first-in-class, targeted immunotherapy agent for treatment of B-cell malignancies with a novel mechanism of action which involves in-vivo engagement of the patient's T cells with CD19-expressing tumour cells. Clinical trials have demonstrated its efficacy in relapsed B-cell Acute Lymphoblastic Leukaemia (B-ALL) and B-cell Non-Hodgkin's Lymphoma including in patients who are refractory to chemotherapy. This review summarises the development and design of Blinatumomab, the outcome of clinical studies demonstrating its efficacy and how to manage the administration, practically, including relevant toxicities. We compare and contrast it to other emerging agents for treatment of B-cell malignancies.